Perancangan Interior Ruang Ibadah Sekunder dan Sekolah Minggu Gereja Reformed Injili Indonesia Cabang Kertajaya di Surabaya - Mishella Naftalie Gunawan (Intra, 2017)
Indonesian Reformed Evangelical Church Kertajaya Branch in Surabaya is one of the growing churches, both physically and spiritually. This church has a very simple and plain room design, does not have adequate storage facilities, especially in secondary worship room for teenage and youth and the sunday school rooms. Through the process of searching data, analyzing the needs of users, finding solutions to the existing problems, and applying everything that has been collected into a design. A design that can provide a good place and means of worship so that worship can work well and the faith or spirituality of the church can be built on the correct foundation of the truth of the Bible and the Lord Jesus Christ. And as a contribution of interior design ideas for GRII Kertajaya that will do the development. Eventually can be evaluated for better results.